Disclosure, reporting and help seeking among child survivors of violence: a cross-country analysis - Audrey Pereira; Amber Peterman; Anastasia Naomi Neijhoft; Robert Buluma; Rocio Aznar Daban; Aminul Islam; Esmie Tamanda Vilili Kainja; Inah Fatoumata Kaloga; They Kheam; Afrooz Kaviani Johnson; M. Catherine Maternowska; Alina Potts; et al. (BMC, 2020)
Abstract Background Violence against children is a pervasive public health issue, with limited data available across multiple contexts. This study explores the rarely studied prevalence and dynamics around disclosure, reporting and help-seeking behaviours of children who ever experienced physical and/or sexual violence. Methods Using nationally-representative Violence Against Children Surveys in six countries: Cambodia, Haiti, Kenya, Malawi, Nigeria and Tanzania, we present descriptive statistics for prevalence of four outcomes among children aged 13-17 years: informal disclosure, knowledge of where to seek formal help, formal disclosure/help seeking and receipt of formal help. We ran country-specific multivariate logistic regressions predicting outcomes on factors at the individual, household and community levels. Results The prevalence of help-seeking behaviours ranged from 23 to 54% for informal disclosure, 16 to 28% for knowledge of where to seek formal help, under 1 to 25% for formal disclosure or help seeking, and 1 to 11% for receipt of formal help. Factors consistently correlated with promoting help-seeking behaviours included household number of adult females and absence of biological father, while those correlated with reduced help-seeking behaviours included being male and living in a female-headed household. Primary reasons for not seeking help varied by country, including self-blame, apathy and not needing or wanting services. Conclusions Across countries examined, help-seeking and receipt of formal services is low for children experiencing physical and/or sexual violence, with few consistent factors identified which facilitated help-seeking. Further understanding of help seeking, alongside improved data quality and availability will aid prevention responses, including the ability to assist child survivors in a timely manner.